PRAGMALINGUISTICS AND HUMOR - Raximova Nazokat Tukhtamurod qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article explores the relationship between pragmatics and humor. The article analyzes the linguistic foundations of humor, its role in communication, and the relationship between humor and pragmatic concepts. Also, the manifestation of pragmatic factors in the language of humor and socio-cultural aspects of communication are considered. The article also covers the importance of humor in the social context, strategies for its use, and the psychological aspects of creating humor in communication.